Islamic Education in Facing the Challenges of Radicalism and Extremism among the Younger Generation - Yus Hermansyah; Zaenal Mukarom; Mohamad Yudiyanto; Rajaminsah Rajaminsah; Djenal Suhara; Ali Al Bustom (Universitas Muhammadiyah Enrekang, 2023)
This research aims to explore the role of Islamic education in facing the challenges of radicalism and extremism among the younger generation. Using a qualitative approach, this study analyzes various strategies implemented by Islamic educational institutions to form a moderate and inclusive religious understanding. The data was obtained through in-depth interviews with educators, scholars, and students in several Islamic schools and Islamic boarding schools in Indonesia. The results of the study show that Islamic education that emphasizes the values of tolerance, social justice, and openness to diversity can play a significant role in preventing radicalization among adolescents. In addition, the active involvement of parents and the community in religious education was also found to be an important factor in shaping the character of the young generation who are resilient to the influence of radical ideology. This study concludes that holistic and contextual Islamic education is indispensable to face the increasingly complex challenges of radicalism and extremism in the modern era.